Estudio de factibilidad para el desarrollo de un sistema de seguimiento y evaluación del plan operativo anual institucional de la Universidad Técnica de Babahoyo - Paredes Caicedo, Fatima Valeria (2020)
The main objective of this research process was to carry out a feasibility study to establish the importance of the development and implementation of a web application as an alternative computer solution to the problems found in the Babahoyo Technical University Baking Unit, in order to strengthen the monitoring and evaluation process of the Institutional Annual Operating Plan. Through the interview with the head of the planning unit, it was found that the use of office automation tools used for this process of monitoring and evaluating the Institutional Annual Operational Plan are not the most appropriate, since it does not allow a correct integration of the information, becoming a laborious and incomplete work.